Making abstract values tangible: how European University Alliances construct their visual identity in the perspective of creativity - Radziej, Robert; Molek-Kozakowska, Katarzyna (Creativity Studies, 2024)
The European University Initiative established 64 transnational alliances of higher education institutions. Each of these European Universities Alliances seeks to align universities to enhance academic excellence and competitiveness of the European Higher Education Area. While branding of higher education institutions has become a professionalized practice, creating a transnational alliance poses challenges beyond traditional academic visual identity. The aim is to map out visual and discursive self-representation patterns of European University Alliances on their websites, involving European values such as for example, international cooperation, student mobility, and inclusivity. Using multimodal discourse analysis, this study examines online construction of academic identities of selected European University Alliances. It analyses (1) composition, colour, and typography used in European University Alliances’ logotypes; (2) the features of photographs and graphics; and (3) the typology of names and keywords in mission statements. The findings highlight the importance of generic imagery and compositional devices evoking positive emotional responses as well as recognizable cultural symbols and colours that align with the values of academia and “Europeanness”.